Effects of vitamin D supplementation on glucose metabolism and pregnancy outcomes in GDM: a systematic review and meta-analysis - Luo, Rong; Wang, Huijing; Cao, Yangli (Frontiers in Medicine, 2026)
ObjectiveThis systematic review and meta-analysis aimed to evaluate the efficacy and safety of vitamin D supplementation on glucose metabolism and pregnancy outcomes in gestational diabetes mellitus (GDM).MethodsTo achieve this, we searched Chinese and English databases (PubMed, EMBASE, Cochrane Library, China National Knowledge Infrastructure, Wanfang Med Online, and VipInfo Chinese Journal Service Platform) up to September 2024. Data were analyzed using Review Manager 5.3 and Stata 15.1, presenting continuous variables as standardized mean difference (SMD) and dichotomous variables as relative risk (RR), both with 95% confidence intervals (CI). The Cochrane tool assessed the risk of bias.ResultsTwenty studies involving 1,737 patients were included. Meta-analysis showed that compared to placebo, vitamin D supplementation significantly reduced fasting glucose (SMD: −1.01, p = 0.0002), 2-h postprandial glucose (SMD: −0.89, p = 0.0002), insulin levels (SMD: −0.64, p < 0.0001), and insulin resistance (SMD: −0.91, p = 0.001). Furthermore, it was associated with lower incidences of cesarean delivery (RR: 0.68, p < 0.0001), forceps-assisted delivery (RR: 0.44, p = 0.02), preterm birth (RR: 0.28, p < 0.0001), postpartum hemorrhage (RR: 0.27, p = 0.01), fetal distress (RR: 0.17, p = 0.004), neonatal asphyxia (RR: 0.22, p = 0.006), macrosomia (RR: 0.34, p = 0.001), and neonatal hyperbilirubinemia (RR: 0.49, p = 0.001). No significant differences were found for amniotic fluid excess (RR: 0.46, p = 0.10) or pre-eclampsia (RR: 0.60, p = 0.38).ConclusionVitamin D supplementation may improve glucose metabolism and reduce adverse pregnancy outcomes in GDM patients. However, the findings should be interpreted with caution due to substantial heterogeneity among studies and the methodological limitations of the included trials. These exploratory results highlight the need for further rigorous research to confirm the effects.